BRCA1 and BRCA2 genes mutations among women with clinical signs of hereditary breast cancer in western Belarus - Savanevich, Alena; Vasilkevich, Maryia; Abdrashitov, Vitalii; Stepuro, Tatiana (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2021)
Background: Breast cancer is the most common malignancy in women. In the countries of Central and Eastern Europe founder mutations in the BRCA1 and BRCA2 genes are responsible for a significant proportion of breast cancer cases; however, regional differences in the frequencies of various mutations may occur. The spectrum and frequency of BRCA1 and BRCA2 mutations among breast cancer patients have not yet been fully explored in Belarus. Aim: In this study, we aimed to estimate the incidence of BRCA1 and BRCA2 causative founder variants in breast cancer female patients with clinical signs of hereditary disease in western Belarus. Materials and Methods: Blood samples from 71 breast cancer female patients with clinical signs of hereditary disease from the western region of Belarus were examined. We studied 13 causative founder variants in BRCA1 (c.5266dupC, c.4035delA, c.5251C>T, c.181T>G, c.676delT, c.68_69delAG, c.3770_3771delAG, c.1687C>T, c.3756_3759delGTCT) and BRCA2 (c.658_659delGT, c.7910_7914delCCTTT, c.3847_3848delGT, c.5946delT) genes characteristic for the population of Central Europe. The study included 22 female patients with early-onset form, 8 individuals with bilateral and 41 women with multiple primary breast cancer. Results: 32 out of 71 patients (45 %) had one of the causative founder variants in the BRCA1 and BRCA2 genes. The most common mutation defined in these genes was BRCA1 c.5266dupC; it was detected in 19 women with breast cancer (27 %). The carrier of the pathogenic BRCA1 allele c.4035delA was confirmed in 8 cases (11 %). BRCA1 gene mutations were found to be significantly more common in presence of two or more signs of genetic predisposition to breast cancer. However, among 50 patients with a family medical history of breast and/or ovarian cancer and clinical signs of hereditary cancer, mutations in the BRCA1 and BRCA2 genes were found only in 24 (48 %) cases. Conclusion: The study showed high incidence of germinal BRCA1 mutations (45 %) among breast cancer patients in the western region of Belarus. Only two BRCA1 mutations (c.5266dupC, c.4035delA) are detectable in approximately 84 % of carriers. It is necessary to continue studying the mutations in the genes associated with development of breast cancer that are typical for Belarusian population, especially in the group of young female patients, since this study has confirmed the genetic predisposition only in every third patient under the age of 50.